2021
DOI: 10.1016/j.istruc.2021.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Cracking behavior of sea sand RC beam bonded externally with CFRP plate

Abstract: CFRP is an alternative technique for cracking control of high-chloride reinforced concrete (RC) beams. This research, therefore, investigates the strength performance and failure mode and cracking behaviour of RC beams incorporated with sea sand bonded externally with the carbon fibre reinforced polymer (CFRP) plate. Sea sand is used as a 100% replacement of fine aggregate. Three batches of RC beams were carried out in this research, including the control beam (no sea sand neither CFRP), RC beam with normal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The authors observed that RC beams constructed with recycled concrete coarse aggregate failed due to longitudinal steel yielding and concrete crushing in the compression zone. In accordance with the load-deflection relationship of beams at the mid span, more beam strength capacity may reduce the deflection [20].…”
Section: Results and Discussion 31 Flexural Performancementioning
confidence: 73%
“…The authors observed that RC beams constructed with recycled concrete coarse aggregate failed due to longitudinal steel yielding and concrete crushing in the compression zone. In accordance with the load-deflection relationship of beams at the mid span, more beam strength capacity may reduce the deflection [20].…”
Section: Results and Discussion 31 Flexural Performancementioning
confidence: 73%
“…Zhou et al [ 33 ] added fibers as reinforcement in coral concrete and obtained a reduction in the cracks in the concrete, which also changed the bond–slip curve. Similarly, Al-Fakih et al [ 34 ] conducted a study on CFRP plates incorporated with sea sand concrete and bonded to RC beams incorporating sea sand bonded with CFRP plates. The results were the DF for all the specimens; however, the CFRP plate increased the stiffness and cracking performance.…”
Section: Research Progressmentioning
confidence: 99%
“…CFRP strengthening has been shown to increase the stiffness and strength performance of flexural members. It is currently a widespread strengthening methodology for RC members with a variety of applications, for example, the strengthening of sea sand RC members [ 4 ].…”
Section: Introductionmentioning
confidence: 99%